The effect of biliary stenting on difficult common bile duct stones - Aslan, Fatih; Arabul, Mahmut; Celik, Mustafa; Alper, Emrah; Unsal, Belkis (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : If common bile duct (CBD) stones (choledocholithiasis) are left untreated, they may cause increases in morbidity and mortality due to several conditions. Aim: In this study, using transient biliary stenting following the failure of an initial endoscopic retrograde cholangiopancreatography (ERCP) session, we aimed to show the effects of making the CBD stones smaller and easier to remove in the following session. Material and methods : In 156 of 1300 (12%) patients with CBD stones, who underwent balloon screening and/or basket lithotripsy following ERCP and CBD cannulation, it was not possible to remove the stones in the first session. Of these 156 patients, 64 (4.9%) were further followed and tested following transient biliary stenting. Results : In the last ERCP following biliary stenting, the maximum stone sizes and stone indices were decreased in 54 (83%) patients and stone fragmentation was observed in 46 (72%) patients. Complete and incomplete removal was obtained in 40 (62.5%) and 24 (37.5%) patients, respectively. Conclusions : Biliary stenting, fragmentation and the reduction in the size of difficult common bile duct stones caused by the first session of ERCP may increase the chance of success in the next session of ERCP.